Collaborative Educational Supervision in Elementary Schools: A Case Study of Professional Culture Development - Idham Sumirat; Ngurah Ayu Nyoman Murniati; Muhammad Prayito (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
Educational supervision plays an important role in developing professional culture in elementary schools; however, its practice often remains hierarchical and less collaborative. This study examines the contribution of collaborative-based educational supervision to the development of professional culture in an elementary school. A qualitative case study approach was employed, involving the principal and teachers through in-depth interviews, observations, and document analysis. Data were analyzed through reduction, categorization, and interpretation to identify patterns of collaboration and professional growth. The findings indicate that collaborative supervision fosters open communication, reflective teaching practices, joint problem-solving, and mutual trust among educators, thereby strengthening the school’s professional culture. It is concluded that partnership-based supervision is more effective than control-oriented approaches in enhancing teachers’ professional engagement. Schools are therefore encouraged to institutionalize structured dialogue forums, peer observation, and continuous professional development programs. This study is limited to a single school context; further research involving broader settings is recommended to enhance the generalizability of the findings.